Zoysiagrass grow-in, thatch management, weed control, and selection of quality genotypes in the U.S. transition zone - McFadden, Daniele (Kansas State University, 2024)
Zoysiagrass (Zoysia spp.) is a warm-season (C₄) turfgrass species that provides a dense, uniform, high-quality playing surface with excellent heat, drought, pest, and wear tolerance compared to many other cool-season turfgrass species. ‘Meyer’ zoysiagrass is commonly used on golf course fairways, tee boxes, and bunker faces in the U.S. transition zone due to enhanced drought tolerance compared to Kentucky bluegrass and improved cold hardiness compared to bermudagrass. ‘Innovation’ zoysiagrass is a newer cultivar that exhibits finer leaf texture and improved density compared to Meyer, but minimal research has been reported on the cultivar since its commercial release. Zoysiagrass, though maintained with reduced inputs for some sites, is intensively maintained on golf courses and athletic fields, and often times home lawns; therefore, thatch accumulation can occur. Further, zoysiagrass is generally established vegetatively by sod, plugs, or sprigs. Because of the slow rate of zoysiagrass establishment, weed competition within the sward often occurs. Summer annual weeds such as crabgrass (Digitaria spp.) and goosegrass (Eleusine indica (L.) Gaertn.) can affect the growth and establishment of zoysiagrass. Following establishment, bermudagrass (Cynodon spp. L.C. Rich.), is one of the problematic weeds within zoysiagrass swards because of the physiological similarities and therefore lack herbicide options for control. Within the last two decades, zoysiagrass breeding programs in the U.S. have focused their efforts on developing new zoysiagrass hybrids that have increased drought, freezing, and pest tolerance, exhibit finer leaf texture, enhanced rooting, and a faster rate of establishment. Therefore, the objectives of this dissertation were to: 1) determine the influence of aerification intensities on thatch levels, rooting, and turfgrass quality of Innovation zoysiagrass; 2) evaluate how nitrogen rate and mowing height influence the establishment rate, turf quality, thatch accumulation, and post-harvest root strength of experimental hybrid ‘DALZ 1808’, Innovation, and Meyer zoysiagrass from sprigs; 3) evaluate how commonly used herbicides affect the weed encroachment, establishment, and rooting of Innovation zoysiagrass when applied immediately following sprigging; 4) investigate a new commercially available herbicide for its effects on bermudagrass control and zoysiagrass safety; and 5) evaluate a set of sixty-nine experimental zoysiagrass hybrids to identify potential for commercial release. Research herein suggests moderate aerification (10 to 27% core removal) can reduce organic matter and increase rooting, while also enhancing turf quality and color compared to nonaerified turf. Nitrogen rate and mowing height can affect thatch accumulation and post-harvest rooting of zoysiagrass; however, the effects from nitrogen rate and mowing height differences vary by zoysiagrass cultivar. Oxadiazon (liquid formulation) can reduce weed pressure and hasten zoysiagrass establishment when applied immediately following sprigging. Sequential applications of a new herbicide containing trifloxysulfuron-sodium and a proprietary safener (metcamifen) tank-mixed with fluazifop-P-butyl can suppress bermudagrass >95% without causing injury to zoysiagrass. Finally, the zoysiagrass breeding study indicates that several experimental entries show promise across a range of environments, with multiple elite experimental lines exhibiting adaptability in the transition zone. The findings within this dissertation will provide insight for turfgrass practitioners on strategic management of zoysiagrass within the transition zone and beyond.
Keywords: Turfgrass; Zoysiagrass; Aerification; Cultural practices; Weed control